PERBANDINGAN PEMBERIAN ADSORBEN CANGKANG TELUR AYAM TERHADAP PENURUNAN BILANGAN ASAM DAN PEROKSIDA MINYAK JELANTAH PADA TEMPERATUR TINGGI DAN RUANG - Rodhiansyah Djayasinga; Khairuni Fitriany (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2021)
Quality improvement of the waste cooking oil can be conducted by reducing levels of acid number and peroxide number. The purpose of this study was to determine the levels of acid number and peroxide number, as well as the effective temperature of mixing chicken egg shell adsorbents to reduce the acid and peroxide levels. This research was an experimental study with two treatments. The first treatment used the waste cooking oil mixed to chicken egg shell adsorbent at high temperature, then stirred and separated into sediment and supernatant, then determined the levels of peroxide and acid number. The second treatment was carried out alike the first treatment procedure but placed at room temperature. As the independent variables in this study were temperatures that divided at high temperature and room temperature. As dependent variable of the study was levels of acid number and peroxide number.. The results of the study were analyzed using an Independent Bivariate T-test. It was found that there were significant differences in the levels of acid and peroxide (p value = 0,000) with a 95% confidence level. Based on univariate analysis test, it is known that the effective temperature is used to reduce the levels of free fatty acids and peroxide in used cooking oil using egg shell adsorbent at room temperature.